2012
DOI: 10.1371/journal.pone.0050293
|View full text |Cite
|
Sign up to set email alerts
|

Density Gradient Centrifugation Compromises Bone Marrow Mononuclear Cell Yield

Abstract: Bone marrow mononuclear cells (BMNCs) are widely used in regenerative medicine, but recent data suggests that the isolation of BMNCs by commonly used Ficoll-Paque density gradient centrifugation (DGC) causes significant cell loss and influences graft function. The objective of this study was to determine in an animal study whether and how Ficoll-Paque DGC affects the yield and composition of BMNCs compared to alternative isolation methods such as adjusted Percoll DGC or immunomagnetic separation of polymorphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 41 publications
1
77
1
Order By: Relevance
“…The 2-week benzene gavage (200 mg/kg, once daily, 5 days per week, for 2 weeks) does not give rise to an obvious change of NF-κB p65 expression with the reduction in blood cell counts and ABCB1B inhibition. One possible explanation is that the BMNC are not actually 100% hematopoietic cells, in which some impurities could disturb the NF-κB p65 expression (Pösel et al, 2012). Another potential explanation is that the phosphorylation of the p65 subunit of NF-κB might genuinely be required for its transcriptional activation (Nazar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The 2-week benzene gavage (200 mg/kg, once daily, 5 days per week, for 2 weeks) does not give rise to an obvious change of NF-κB p65 expression with the reduction in blood cell counts and ABCB1B inhibition. One possible explanation is that the BMNC are not actually 100% hematopoietic cells, in which some impurities could disturb the NF-κB p65 expression (Pösel et al, 2012). Another potential explanation is that the phosphorylation of the p65 subunit of NF-κB might genuinely be required for its transcriptional activation (Nazar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its long history of use in lab-oratories, there are some pitfalls associated to this technique, such as the possible loss of tumor cells that migrate either to the plasma fraction or to the bottom of the gradient due to the formation of aggregates (22 ). It has been suggested that this cell loss may be due to the cytotoxicity of the density medium (23 ). An alternative to Ficoll is Percoll density (GE Healthcare Life Sciences) gradient medium made of a colloidal silica particle suspension.…”
Section: Methods Based On Physical Propertiesmentioning
confidence: 99%
“…An alternative to Ficoll is Percoll density (GE Healthcare Life Sciences) gradient medium made of a colloidal silica particle suspension. The main advantages over Ficoll include reduced toxicity and a wider density gradient range (23 ). There are certain discrepancies in the literature regarding the use of Percoll because some studies have demonstrated a high purity rate (24 ) while others have shown low isolation efficiencies compared to Ficoll (25 ).…”
Section: Methods Based On Physical Propertiesmentioning
confidence: 99%
“…In accordance with multiple studies such cell mixture promotes distinct angiogenic properties, mediates vascular repair, express several cytoprotective growth factors and cytokines [13]. Practically BMC intravenous transplantation dramatically increases level of blood BMC concentration up to concentration which can't be reached by another experimental procedure.…”
Section: Resultsmentioning
confidence: 53%